1981
DOI: 10.1111/j.1365-2621.1981.tb04486.x
|View full text |Cite
|
Sign up to set email alerts
|

A Microscopical Study of the Structure of Meat Emulsions and Its Relationship to Thermal Stability

Abstract: Meat emulsions were examined by light microscopy to determine the relationships between structure and emulsion stability. Beef-meat based emulsions were prepared either by varying chopping temperature or by adding soy plastic fats of different hardness. Formation of fat channels was observed in uncooked emulsions prepared either at a cho ping temperature of 26°C or with soft plastic fat of 0.25cm-4 hardness index. Such fat channel formations caused discontinuity of protein matrix, leading to fat separation dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…These observed microstructural characteristics may be due to low fat-and water-binding capacity of WGF additive in the meat system under these processing conditions. Similar results were observed in meat emulsion products with com germ flour and soy flour as additives (Lee et al 1981;Lin and Zayas 1987). These authors reported that micrographs showed void spaces and lack of compacted protein fat matrix in the wieners.…”
Section: Water Activity (Aw) Compression Force and Shear Forcesupporting
confidence: 77%
“…These observed microstructural characteristics may be due to low fat-and water-binding capacity of WGF additive in the meat system under these processing conditions. Similar results were observed in meat emulsion products with com germ flour and soy flour as additives (Lee et al 1981;Lin and Zayas 1987). These authors reported that micrographs showed void spaces and lack of compacted protein fat matrix in the wieners.…”
Section: Water Activity (Aw) Compression Force and Shear Forcesupporting
confidence: 77%
“…This organisation favours a break in the emulsion with rupture of the globules and consequent coalescence. According to the theory of a non-emulsion, the fat becomes physically enclosed in the protein matrix in this case, but only a minimal portion appears embedded in the matrix (Barbut, 2008;Lee, Carrol, & Abdollahi, 1981). Thus, the break in the structure includes the separation of fat and excretion of water from the matrix with denaturation and coagulation of the meat proteins due to heating (Aguilera & Stanley, 1990).…”
Section: Microstructural Analysismentioning
confidence: 96%
“…Thus, the break in the structure includes the separation of fat and excretion of water from the matrix with denaturation and coagulation of the meat proteins due to heating (Aguilera & Stanley, 1990). This characteristic in the F0 formulation may be due to the use of fat (chicken breast skin) in the liquid form, which may cause destabilization of the meat emulsion, because mobility is inversely proportional to consistency (Lee, Carrol, & Abdollahi, 1981). In addition, the proportion of starch used (2 g/100 g) was not sufficient to form a stable emulsion in the formulation without ARB.…”
Section: Microstructural Analysismentioning
confidence: 99%
“…Lee et al (1981) found some fat globules can be present at > 20 µm in diameter suggesting comminuted meat systems should also in some circumstances be explained by the gelation theory. The gelation theory is described by Lee et al (1981) as continuous protein gel matrix.…”
Section: Protein-fat Interactionsmentioning
confidence: 99%
“…Lee et al (1981) found some fat globules can be present at > 20 µm in diameter suggesting comminuted meat systems should also in some circumstances be explained by the gelation theory. The gelation theory is described by Lee et al (1981) as continuous protein gel matrix. The protein gel matrix is different from an emulsion in the interfacial film is the result of protein absorption on the surface of globule which is surrounded by a continuous liquid phase (Barbut, 1995).…”
Section: Protein-fat Interactionsmentioning
confidence: 99%